Cultura y salud: integrando extensión, docencia e investigación. (FAVE Sección Ciencias Veterinarias, 2022)
This article reports on a path composed of the articulation and integration of extension with teaching and research in university degree education in the veterinary medicine career of the UNL. The partner of the extension project is the public health system of the city of Esperanza (Province of Santa Fe) with which it has been agreed to carry out cultural activities derived from social demands and exploratory research on the perceptions of the community, carried out by students of said career as part of their professional training.
Keywords: integration of functions, extension, culture, health, social perceptions